The effect of cognitive task difficulty and articulation on postural sway - Rezvan Azimi; Behrouz Abdoli; Mohammad Ali Sanjari; Reza Khosrowabadi (University of Tehran, 2022)
Introduction: Many studies evaluate the interaction between cognition and posture but the effect of cognitive task difficulty and articulation on postural control remains inconclusive. The purpose of the present study was to examine the interaction effect of cognitive task difficulty and articulation on postural control.Methods: Twenty healthy young volunteers (Mean age 22 ± 2.3 years) performed four random conditions while standing on a force platform. Conditions involved combinations of two level of cognitive task difficulty (easy and difficult cognitivetask) and two level of verbal response (simultaneous and final).Results: Two-way ANOVA (significant level P<0.05) results demonstrated marked increased in the standard deviation and area of 95% confidence ellipse of the center of pressure in the difficult cognitive task condition with simultaneous verbalresponse. (P<0.05). Also, in the final response condition, difficult cognitive task reduced area of 95% confidence ellipse.Conclusion: According to the results of the present research, it seems that the difficult cognitive task requires a greater part of attention capacity; subsequently,attention is withdrawn from the postural task and automatic control regulates posture more efficiently through unconscious, fast, and reflexive processes. Also, postural control is simultaneously affected by the difficulty of cognitive task and articulation.Therefore, for designing appropriate interventions, it seems necessary to pay attention to the interactive effects of the difficulty and articulation of cognitive task.